Site Specific Opera : a Re-imagined Magic Flute as a Catalyst to the Narration of Fort Daspoortrand Heritage - Jekot, Barbara (University of Pretoria, 2018)
Mini-dissertation Mint(Prof)--University of Pretoria, 2018.